Retrospective cohort study on primary school dropout children of Chitwan and Nawalparasi districts of Nepal (Global Journal of Human-Social Science, 2012)
The formal education in Nepal starts from pre-primary level to higher secondary level The primary level consists of grades I to V Any student who leaves school for any reason before graduation or completion of a program of studies without transferring to another elementary or secondary school is considered as primary school dropout Objectives of the study are to find out the primary school completion rate and causes of dropout in primary schools of Chitwan and Nawalparasi district of Nepal A retrospective cohort study was conducted in fifteen schools in each district during the period of June July 2010 In grade I the maximum dropout rate was found to be 16 49 in the year 2008 For the girls the highest dropout rate 9 96 was observed in grade I and least dropout rate 3 94 observed in grade V for the year 2009 From the cohort study only 48 99 of primary school children enrolled in grade I have completed the primary education in five successive years
Keywords: Education; completion; cohort; enrolled